Biological injection therapy with leukocyte-poor platelet-rich plasma induces cellular alterations, enhancement of lubricin, and inflammatory downregulation in vivo in human knees: A controlled, prospective human clinical trial based on mass spectrometry imaging analysis - Baltzer, Axel W.; Casadonte, Rita; Korff, Alexei; Baltzer, Lea Merline; Kriegsmann, Katharina; Kriegsmann, Mark; Kriegsmann, Jörg (Frontiers in Surgery, 2023)
Objective: To investigate the in-vivo biological effects of Leukocyte-poor-Platelet-Rich-Plasma (LpPRP) treatment in human synovial layer to establish the cellular basis for a prolonged clinical improvement. Methods: Synovial tissues (n=367) were prospectively collected from patients undergoing arthroscopic surgery. Autologous-Conditioned-Plasma, LpPRP, was injected into the knees of 163 patients 1-to-7 days before surgery to reduce operative trauma and inflammation, and to induce the onset of regeneration. 204 patients did not receive any injection. All samples were analyzed by mass spectrometry imaging. Data analysis was evaluated by clustering, classification, and investigation of predictive peptides. Peptide identification was done by tandem mass spectrometry and database matching. Results: Data analysis revealed two major clusters belonging to LpPRP-treated (LpPRP-1 and -untreated (LpPRP-0) patients. Classification analysis showed a discrimination accuracy of 82-90%. We identified discriminating peptides for CD45 and CD29 receptors (receptor-type-tyrosine-protein phosphatase-C and integrin-Beta-1), indicating an enhancement of Musculo Skeletal Stem Cells, as well as an enhancement of lubricin, collagen-alpha-1-(I) chain and interleukin-receptor-17-E, dampening the inflammatory reaction in the LpPRP-1 group following LpPRP injection. Conclusions: We could demonstrate for the first time that injection therapy using “autologic-conditioned-biologics” may lead to cellular changes in the synovial membrane that might explain the reported prolonged beneficial clinical effects. Here, we show in-vivo cellular changes, possibly based on MSC alterations, in the synovial layer. The gliding capacities of joints might be improved by enhancing of lubricin, anti-inflammation by activation of interleukin-17-receptor-E, and reduction of the inflammatory process by blocking interleukin-17.